Outcomes of enucleation and porous polyethylene orbital implant insertion in patients with paediatric retinoblastoma: a long-term follow-up study. Issue 4 (8th December 2020) - Yang, Min Kyu; Lee, Min Joung; Kim, Namju; Choung, Hokyung; Khwarg, Sang In
Abstract : Background/Aims: To report the long-term outcomes of enucleation and insertion of porous polyethylene (PP) orbital implant according to the evolving surgical techniques and implant in patients with paediatric retinoblastoma . Methods: Patients with paediatric retinoblastoma who underwent enucleation and PP implant insertion from December 1998 to December 2014 were retrospectively reviewed and divided into four groups: group A, classic enucleation +PP implant; group B, enucleation +PP implant +anterior closure of the posterior Tenon's (ACPT) capsule; group C, enucleation +PP implant +free orbital fat graft +ACPT and group D, enucleation +smooth surface tunnel PP implant +ACPT. Survival analysis of implant exposure and eyelid malpositions was performed. Results: One hundred and ninety-eight eyes of 196 patients were included. The median follow-up period was 13.0 years (range, 5.0–21.1). A 20 mm implant was inserted for 149 eyes (75.3%). The 10-year exposure-free survival probabilities were 44.6% in group A, 96.4% in group B, 97.4% in group C and 97.7% in group D. ACPT was associated with significant reduction in implant exposure (p<0.001). The most common eyelid malposition was upper eyelid ptosis (24.2%). The eyelid malposition-free survival probability did not differ among the four groups. However, the insertion of a 20 mm implant was associated with significant reduction in upper eyelid ptosis and lower eyelid entropion (p=0.004 and 0.038, respectively). Conclusions: The long-term postenucleation implant exposure was rare after PP implant insertion and ACPT, even with a 20 mm-diameter implant. A larger implant can be beneficial in long-term prevention of eyelid malposition.